A study on purchase intention towards convenience food products in Malaysia - Chua, Ti Ling; Lau , Janice; Lee, Mei Hui (2017)
Convenience food products have become the choice of many Malaysians due to the increase in their standard of living and purchasing power. The changes of Malaysians' lifestyle have resulted in an increase in the demand for convenience food which in turn leads to innovative new products in the food processing. This research aim to study the factors which include advertisement, brand awareness, perceived value, price, and place that influence the purchase intention towards convenience food products in Malaysia. Throughout this study, non-probability sampling technique were employed to collect the data from respondents via internet. A total of 324 responses from respondents were successfully collected. However, there are only 300 responses suitable to proceed for further analysis for this study. In order to ensure the research data are reliable, primary data (questionnaire) and secondary data were adopted in this study. A total 3 analysis comprises of descriptive analysis, reliability test and inferential analysis (Pearson Correlation Analysis and Multiple Linear Regression) was obtained through the Statistical Package for Social Science (SPSS) version 23.0. The result obtained from the analysis has been tabulated and discussed in details in the Chapter 4 of this study. In the end of the study, the limitations encounter by researchers and recommendations suggested for future researches has been discussed in Chapter 5. In the end of this research, it showed that advertisement, perceived value, and price has significant effect towards the purchase intention towards convenience food products in Malaysia. Whereas, brand awareness and place has insignificant relationship with the purchase intention towards convenience food products in Malaysia. In conclusion, it hoped that this research finding able to provide some useful information for Malaysia’s government organisation in order to take initiative for concerning the nation health problem as well as creating the health awareness to public.